TATHWÎR NAMÛDZAJ AL-MUQARRAR AL-DIRÂSÎ LI MÂDAH TASHMÎM TADRÎS AL-LUGHAH AL-‘ARABIYYAH ‘ALÂ ASÂS AL-NASYÂTHÂT - Raswan, Raswan (Arabi : Journal of Arabic Studies, 2017)
This research was aimed to develop syllabus of Arabic Learning Planning course. The syllabus to be developed is a syllabus that enables the students to develop good planning in learning Arabic language based on both the theory of unity (All in One System / نظرية الوحدة) and branch theory (نظرية الفروع). The design of learning is essentially a skill; therefore the learning should be activity-based. If not, the students who study development will not be proficient. This paper discussed a syllabus model that is able to develop Arabic learning designs for madrasah, schools and pesantren in which Arabic language is taught and activity-based.